2020
DOI: 10.4491/eer.2020.189
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of persulfate and simulated sunlight radiation on azithromycin removal

Abstract: Azithromycin (AZT) is a macrolide antibiotic whose presence in different bodies of water has been reported. This implies that conventional treatment systems are not able for AZT removal. This paper presents the main results regarding the potential use of simulated sunlight and persulfate (PS) on the removal of AZT. The effects of the solution pH and the concentration of PS were evaluated considering a face centered, central composite experimental design. Under optimized experimental conditions, it was possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The major findings on the possible use of simulated sunshine and persulfate (PS) to remove AZY were presented in [105]. A face-centered, central composite experimental design was used to obtain the effects of solution pH and PS concentration.…”
Section: Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major findings on the possible use of simulated sunshine and persulfate (PS) to remove AZY were presented in [105]. A face-centered, central composite experimental design was used to obtain the effects of solution pH and PS concentration.…”
Section: Antibioticsmentioning
confidence: 99%
“…As a result of GO@Fe 3 O 4 /ZnO/strong SnO 2 's capacity to remove azithromycin, this molecule can be employed as an efficient photocatalyst for the degradation of antibiotics in aqueous solutions. The major findings on the possible use of simulated sunshine and persulfate (PS) to remove AZY were presented in [105]. A face-centered, central composite experimental design was used to obtain the effects of solution pH and PS concentration.…”
Section: Antibioticsmentioning
confidence: 99%
“…Kumar et al [ 16 ] reported 98.4% AZT photodegradation in 90 min under visible light using a Ag@Bi 4 O 5 I 2 /SPION@calcium alginate catalyst. Ospino-Atehortúa et al [ 17 ] used persulfate and simulated sunshine achieving about 70% of AZT photodegradation in 120 min of irradiation in basic pH. Tenzin et al [ 18 ] utilized SrTiO 3 for the photodegradation of AZT under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%